Hadith #2271 - Sunan Abi Dawud - Ahmed bin Salah al-Masri أحمد بن صالح المصري; Aisha bint Abi Bakr; Anbs'h bin Khalid bin Yazid عنبسة بن خالد بن يزيد; Muhammad Ibn Maslama; Urwa ibn al-Zubayr عروة بن الزبير; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
Khalil or Ibn Khalil said “A woman was brought to Ali bin Abi Talib(may Allaah be pleased with him). She bore a child from intercourse of three persons. The narrator transmitted the rest of the tradition similar to the previous one. But in this version he did not mention “Yemen” and the Prophet (ﷺ) and his words “give the child willingly.”
Grade: Hasan

Hadith #2913 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad Ibn Maslama; Musa bin Da'ud al-Dby موسى بن داود الضبي أبو عبد الله; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan Abi Dawud)
Mu’adh bought the property of a Jew whose heir was a Muslim. He then narrated from the Prophet (ﷺ) to the same effect.
Grade: Da'if

Hadith #3163 - Sunan Abi Dawud - al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Jabir ibn 'Abdullah; Muhammad bin Hatm bin Bzy' محمد بن حاتم بن بزيع; Muhammad Ibn Maslama (Sunan Abi Dawud)
I saw the Messenger of Allah (ﷺ) that he kissed Uthman ibn Maz’un while he was dead, and I saw that tears were flowing (from his eyes).
Grade: Sahih

Hadith #3608 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Muhammad Ibn Maslama; Salmah bin Shbyb سلمة بن شبيب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) gave a decision on the basis of an oath and a single witness.
Grade: Sahih

Hadith #4448 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Muhammad Ibn Maslama; Unbasa bin Sa'id bin al-Aas عنبسة بن سعيد بن العاص بن سعيد; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The people passed by the Messenger of Allah (ﷺ) with a Jew who was blackened with charcoal and who was being flogged. He called them and said: Is this the prescribed punishment for a fornicator? They said: Yes. He then called on a learned man among them and asked him: I adjure you by Allah Who revealed the Torah to Moses, do you find this prescribed punishment for a fornicator in your divine Book? He said: By Allah, no. If you had not adjured me about this, I should not have informed you. We f
Grade: Sahih

Hadith #4544 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Ikrama عكرمة; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Muhammad Ibn Maslama; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
I read out to Sa’id b. Ya’qub al-Taliqini who said: Abu Tumailah transmitted to us, saying: Muhammad b. Ishaq transmitted to us saying: ‘Ata reported Jabir b. ‘Abd Allah as saying: The Messenger of Allah (ﷺ) fixed; and he mentioned the tradition like that of Musa; he said: And those who possess corn food should pay something which I do not remember.
Grade: Da'if